Importance of latrine communication in European rabbits shifts along a rural–to–urban gradient. Issue 1 (December 2016) - Ziege, Madlen; Bierbach, David; Bischoff, Svenja; Brandt, Anna-Lena; Brix, Mareike; Greshake, Bastian; Merker, Stefan; Wenninger, Sandra; Wronski, Torsten; Plath, Martin
Abstract Background Information transfer in mammalian communication networks is often based on the deposition of excreta in latrines. Depending on the intended receiver(s), latrines are either formed at territorial boundaries (between -group communication ) or in core areas of home ranges (within -group communication ). The relative importance of both types of marking behavior should depend, amongst other factors, on population densities and social group sizes, which tend to differ between urban and rural wildlife populations. Our study is the first to assess (direct and indirect) anthropogenic influences on mammalian latrine-based communication networks along a rural-to-urban gradient in European rabbits (Oryctolagus cuniculus ) living in urban, suburban and rural areas in and around Frankfurt am Main (Germany). Results The proportion of latrines located in close proximity to the burrow was higher at rural study sites compared to urban and suburban ones. At rural sites, we found the largest latrines and highest latrine densities close to the burrow, suggesting that core marking prevailed. By contrast, latrine dimensions and densities increased with increasing distance from the burrow in urban and suburban populations, suggesting a higher importance of peripheral marking. Conclusions Increased population densities, but smaller social group sizes in urban rabbit populations may lead to an increased importance ofbetween -group communication and thus, favor peripheral over core marking. Our study provides novel insights into the manifold ways by which man-made habitat alterations along a rural-to-urban gradient directly and indirectly affect wildlife populations, including latrine-based communication networks.